2019
DOI: 10.1248/bpb.b18-00343
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour Effect and Pharmacokinetics of an Active Ingredient Isolated from <i>Inonotus hispidus</i>

Abstract: Inonotus hispidus is an anti-tumour drug used in folk medicine. (4S,5S)-4-Hydroxy-3,5-dimethoxycyclohex-2-enone (HDE) is a compound isolated from Inonotus hispidus for the first time. However, the mechanisms underlying its therapeutic effects have not been elucidated. In this study, the in vitro screening, in vivo anti-tumour effects, mechanism of action, pharmacokinetics, and tissue distribution of HDE were investigated. HDE could inhibit the proliferation of HepG2 cells. Additionally, its half-maximal inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In their experiments to examine the fatty acid composition of fruiting bodies, Zan et al discovered two hydrocarbons, squalene ( 56 ) and docosane ( 57 ), and one phthalate, 1,2-benzenedicarboxylic acid mono(2-ethylhexyl) ester ( 58 ) [ 15 ]. In the separation of anticancer active components, Yang et al isolated a new compound from the methanol extract of fruiting bodies in 2019 and confirmed its structure as (4S,5S)-4-Hydroxy-3,5-dimethoxycyclohex-2-enone (HDE, 59 ) by LC-MS and NMR [ 27 ]. When analyzing the methanol extract composition of I. hispidus fruiting bodies, Yang et al identified a nucleoside compound, inosine ( 60 ), based on a comparison of UV absorption characteristics and retention time with a standard [ 20 ].…”
Section: Compounds With Diverse Structuresmentioning
confidence: 99%
“…In their experiments to examine the fatty acid composition of fruiting bodies, Zan et al discovered two hydrocarbons, squalene ( 56 ) and docosane ( 57 ), and one phthalate, 1,2-benzenedicarboxylic acid mono(2-ethylhexyl) ester ( 58 ) [ 15 ]. In the separation of anticancer active components, Yang et al isolated a new compound from the methanol extract of fruiting bodies in 2019 and confirmed its structure as (4S,5S)-4-Hydroxy-3,5-dimethoxycyclohex-2-enone (HDE, 59 ) by LC-MS and NMR [ 27 ]. When analyzing the methanol extract composition of I. hispidus fruiting bodies, Yang et al identified a nucleoside compound, inosine ( 60 ), based on a comparison of UV absorption characteristics and retention time with a standard [ 20 ].…”
Section: Compounds With Diverse Structuresmentioning
confidence: 99%
“… 2 Previous chemical studies showed that it produced a series of active compounds such as polysaccharides, polyphenols, triterpenes, sterols, and melanin. 1 , 3 , 4 Recent investigations have revealed that fruiting body extracts of I. hispidus have antitumor, 5 , 6 antiviral, 7 immunomodulatory, 8 antioxidant, 9 and hypolipidemic activities. 10 The I. hispidus mushroom has great application value and development potential in the field of functional food and medicine in the future.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Extracts of I. hispidus have been reported to possess a wide range of beneficial properties including antiviral activity, antioxidant activity, antitumor, immunomodulation activities and hypolipidemic activity. [36][37][38][39][40][41][42] Inonotus hispidus extracts have also been shown to provide a protective effect for acute alcoholic liver injury. 43 A number of studies have sought to identify bioactive ingredients such as polysaccharides, triterpenoids and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of I . hispidus have been reported to possess a wide range of beneficial properties including antiviral activity, antioxidant activity, antitumor, immunomodulation activities and hypolipidemic activity 36‐42 . Inonotus hispidus extracts have also been shown to provide a protective effect for acute alcoholic liver injury 43 .…”
Section: Introductionmentioning
confidence: 99%